Reduction of Waste Smelter Slags using Top-submerged Injection of Gases - Yan, X Yong; Li, Nan; Grimsey, Eric (Iron and Steel Society (ISS), 1996)
The top-submerged injection method has been used to introduce methane and air mixtures into a waste smelter slag to reduce the dissolved nickel, cobalt and cuprous oxides. A number of parameters affecting the reduction rate have been investigated. These are total gas flowrate, methane to air ratio, temperature, slag composition, orifice size and immersion depth of the lance. The results show that the reduction is enhanced with increase in the methane-to-air ratio, and by using a smaller orifice and deeper immersion of the lance. The maximum metal reductions achieved were 90 percent for nickel, 70 percent for cobalt, and 55 percent for copper, with ten percent of the gas achieving equilibration with the slag under these conditions.